2012
DOI: 10.3354/meps09648
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of the neon damselfish Pomacentrus coelestis indicates a cryptic species and different species origins in the West Pacific Ocean

Abstract: While the center of the world's marine biodiversity is undoubtedly the central West Pacific, the mechanisms by which such high biodiversity was generated and perpetuated are still under debate. In this study, we amplified both a mitochondrial DNA control region and 4 microsatellite loci to elucidate the historical phylogeography of the neon damselfish Pomacentrus coelestis in the West Pacific and used the distribution of alleles to test the 'Center of Origin' hypothesis. Two deeply divergent clades ('Pacific' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 65 publications
4
19
0
Order By: Relevance
“…, ; Drew & Kaufman ; Liu et al. ; Bernardi ). We now know that the evolutionary mosaic of marine species is much more finely partitioned and that factors such as local ecological conditions can play a major role in the evolutionary history of fishes (Rocha et al.…”
Section: Introductionmentioning
confidence: 99%
“…, ; Drew & Kaufman ; Liu et al. ; Bernardi ). We now know that the evolutionary mosaic of marine species is much more finely partitioned and that factors such as local ecological conditions can play a major role in the evolutionary history of fishes (Rocha et al.…”
Section: Introductionmentioning
confidence: 99%
“…In this study we investigate the latitude‐wide genetic patterns of a common coral reef fish, the neon damselfish species complex ( Pomacentrus coelestis ). A previous study of the neon damselfish reported the existence of two genetically divergent, yet morphologically cryptic lineages (Liu et al ). The authors describe a Micronesian clade (re‐described as Pomacentrus micronesicus in Liu et al ) that is found at low latitudes, but co‐occurs in parts of the Coral Triangle with another widespread clade ( P. coelestis ; herein referred to as the Pacific clade sensu Liu et al ; Fig.…”
mentioning
confidence: 99%
“…some taxa show nearly reciprocal monophyly in mtDNA over relatively short distances, probably as a consequence of isolation during the Pleistocene (e.g., barber et al 2000,2002). For many taxa, interestingly, the locations of likely vicariance due to Pleistocene sea level change are also associated with regions of persistent population genetic structure, most notably the sunda shelf (McMillan et al 1999, Deboer et al 2008, Ackiss et al 2013, torres strait (Mirams et al 2011), and Halmahera Eddy (barber et al 2006, 2011), although there is also evidence that this structure is being eroded by contemporary dispersal in some species , Liu et al 2012, Deboer et al 2014. Finally, nearly all loci and taxa that have been examined to date show signatures of Pleistocene-era population expansions onto newly submerged continental shelf habitats (e.g., chenoweth et al 1998, Lind et al 2007, crandall et al 2008a,b, 2012a, Gaither et al 2010.…”
mentioning
confidence: 99%